Association between mean arterial pressure and neurological outcome in survivors of a cardiac arrest undergoing targeted temperature management. (14th October 2021) - Vasserot, I; Severo, A; Juarez, V; Rivero, B; Arbas, E; Poveda, D; Tebar, D; Merino, C; Marco, I; Martin, L; Garcia-Arribas, D; Caro, J; et al.
Abstract: Background: Besides targeted temperature management (TTM), no other therapeutic strategy has shown to improve neurological outcome in cardiac arrest patients. Recently, it has been suggested that higher levels of mean arterial blood pressure (>90 mmHg) may have a protective neurological effect in this population, yet data is scarce. Objective: To describe the association between neurological outcomes and MAP during TTM. Methods: Retrospective study of a prospective database including survivors of a cardiac arrest undergoing TTM and admitted to the acute cardiac care of a tertiary university hospital from September 2007 to July 2020. MAP was recorded from arrival and hourly during TTM. Neurological outcome was graded 3 months after initial event using the Pittsburgh Cerebral Performance Category (CPC) scale and patients were divided classified as follows: Group A patients with CPC of 1 to 2 (good neurological outcome), and group B, with CPC 3 to 5 (poor neurological outcome or death). As CPC 5 comprises patients who have died but whose cause of death may not be related to their neurological condition, we sort to control this potential source of bias, by including a variable of "severe neurological injury", which includes patients with CPC 3–4 and those CPC 5 who died due to WLST due to poor neurological prognosis/brain death. Results: A total pf 431 patients were analysed. Baseline and cardiac arrest characteristics are depicted in Table 1. Patients in group B had a higher proportion of non-witnessed cardiac arrest, out-of-hospital cardiac arrest, non-shockable rhythm, and longer time before ROSC. The relation between MAP and neurological outcome is shown in Table 2. The were no differences of MAP in day 1 and 3 between groups. MAP was statistically higher in Group A during day 2 or rewarming phase. Mean MAP during day 1 and 2; and during day 1, 2 and 3 was also significantly higher in group A. However, when same analysis was performed under the variable "severe neurological injury" no statistically significant differences were observed. Conclusion: There is no association between MAP and neurological outcomes, when true "severe neurological injury" is analysed. Therefore, and until further data is obtained, following actual practical guidelines or avoiding hypotension seems to be the goal in this population, as higher MAP may also have deleterious effects. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): University Hospital La Paz